THE REVOLUTION OF OUR UNDERSTANDING OF DOMESTIC WORK: THE CONSTITUTIONAL CASE OF Mahlangu v Minister of Labour [2020] ZACC 24 - Zulu, Thuli (Obiter, 2024)
This case note studies the effects of the case of Mahlangu v Minister of Labour ([2020] ZACC 24) (Mahlangu) on domestic work. It argues that the historical and colonial understanding of domestic work is premised on slavery and servitude, and so the understanding of domestic work is one that for centuries has rendered Black women who perform this work invisible. This case note shows how the Mahlangu judgment has revolutionised our understanding of domestic work. It further argues that the exclusion of domestic work from the Compensation for Occupational Injuries and Diseases Act (130 of 1993) (COIDA) overlooked domestic work as a type of employment worthy of compensation. The Mahlangu judgment has effected changes to COIDA, allowing for the definition of “employee” to include domestic workers. Lastly, the case note shows that this inclusion is a step forward in regulating domestic work effectively as a form of legitimate employment and further humanising women who make up the large majority of those that do this work.